Extension of Tao-Mason Equation of State to Heavy n-Alkanes - Yousefi, Fakhri; Karimi, Hajir; Papari, Mohammad Mehdi (Chinese journal of chemical engineering, 2013)
In our previous paper we extended the Tao and Mason equation of state （TM EOS） to refrigerant fluids, using the speed of sound data. This is a continuation for evaluating TM EOS in predicting PVT properties of heavy n-alkanes. Liquid density of long-chain n-alkane systems from C 9 to C 20 have been calculated using an analytical equation of state based on the statistical-mechanical perturbation theory. The second virial coefficients of these n-alkanes are scarce and there is no accurate potential energy function for their theoretical calculation. In this work the second virial coefficients are calculated using a corresponding state correlation based on surface tension and liquid density at the freezing point. The deviation of calculated densities of these alkanes is within 0.5% from experimental data. The densities of n-alkanes obtained from the TM EOS are compared with those calculated from Ihm-Song-Mason equation of state and the corresponding-states liquid densities （COSTALD）. Our results are in favor of the preference of the TM EOS over other two equations of state.